Feasibility of everolimus-eluting bioresorbable vascular scaffolds in patients with chronic total occlusion. (20th January 2015) - Wiebe, Jens; Liebetrau, Christoph; Dörr, Oliver; Most, Astrid; Weipert, Kay; Rixe, Johannes; Bauer, Timm; Möllmann, Helge; Elsässer, Albrecht; Hamm, Christian W.; Nef, Holger M.
Abstract: Objective: This study evaluates the feasibility of percutaneous coronary intervention with bioresorbable vascular scaffolds (BVSs) in chronic total occlusion (CTO) lesions. Background: Everolimus-eluting BVSs represent a new approach to treating coronary artery disease, but experience with CTO is limited. Methods: Patients with a previously diagnosed CTO who had been treated with BVS were included. Patients with unsuccessful CTO procedures and patients treated with drug-eluting stents were excluded. Difficulty of the CTO procedure was assessed by the J-score. Results: A total of 23 patients were included. Mean age was 60.4 ± 9.0 years, 17.4% were female, 91.3% suffered from hypertension and 34.8% from diabetes. Mean J-score was 1.7 ± 1.0. Median procedure time was 70 min (54–85), mean contrast volume was 213.5 mL (± 94.2) and median fluoroscopy time was 19.1 min (13.1–30.0). A total of 64 BVSs were implanted with a mean number of 2.8 ± 1.0 BVSs per patient, a mean total BVS length of 64.8 ± 24.2 mm per lesion, and a mean BVS diameter of 3.1 ± 0.2 mm. Neither a scaffold-related dissection nor any other intra-procedural complication occurred. During a follow-up of 108 (79.5–214.5) days one in-scaffold thrombosis was noted 4 days after the CTO procedure due to a lack of dual antiplatelet therapy. No further major adverse cardiac events occurred. Conclusion: These results suggest that BVS implantation in CTO lesions can be performed with good procedural success and reasonable clinical short-term outcome in highly selected cases. Highlights: Patients with a diagnosed CTO who had been treated with BVS were included. Patients with unsuccessful CTO procedures were excluded. Patients treated with drug-eluting stents were excluded. Difficulty of the CTO procedure was assessed by the J-score. BVS implantation in CTO lesions can be performed with good procedural success.